Islamic Sharia Between Aceh And The Middle East - Abdurrazak, Abdurrazak; Fajri, Akmal (An-Nahdah Al-'Arabiyah, 2024)
Islamic Sharia in its implementation in Aceh and the Middle East is full of issues that hinder its implementation. Human rights issues are one form of obstacles and contradictions that are often faced in the implementation of Islamic law in Aceh and the Middle East. In this article, we analyze how Islamic Sharia is implemented in Aceh and the Middle East as well as the obstacles and contradictions faced by the governments of Aceh and the Middle East. The research method used to analyze the problem is using qualitative descriptions with library research data collection techniques. The results obtained from data analysis are that Aceh implemented the Qanun Jinayat which was structured in such a way that there were no elements that would undermine human rights (HAM). In this case, everything has been prepared in law and Qanun Jinayat with the aim of maintaining and respecting human values in Aceh so that the people in Aceh are not oppressed, and in successful implementation it is important to involve Aceh traditional institutions. Meanwhile, in the Middle East, the application of Islamic law is the main basis for establishing law. This is because the Koran and Hadith are the highest law in the Middle East or in other words the law of heaven.